2021
DOI: 10.1016/j.diabres.2021.109069
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of blood pressure and pulse rate by switching from DPP-4 inhibitor to luseogliflozin in patients with type 2 diabetes complicated with hypertension: A multicenter, prospective, randomized, open-label, parallel-group comparison trial (LUNA study)

Abstract: Sodium-glucose cotransporter-2 inhibitor (SGLT2i) reduces clinic blood pressure (BP), but the effects on BP circadian rhythm remain unclear. The present study aimed to determine the nighttime antihypertensive effect of SGLT2i compared with dipeptidyl peptidase-4 inhibitor (DPP-4i) in patients with type 2 diabetes and hypertension. Materials and Methods: In this randomized, open-label, parallel-group trial, patients treated with DPP-4i were either switched to luseogliflozin 2.5 mg/day (Luseo group; n = 30) or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Furthermore, studies have shown that both DPP-4is and SGLT2is exhibit a renal protective effect to reduce renal albumin and either improve or ameliorate the decrease in eGFR [ 30 32 ]. Administration of luseogliflozin decreased heart rate in Japanese patients with T2DM with higher heart rate [ 33 ], and switching from DPP-4is to luseogliflozin has been shown to decrease nighttime pulse rate [ 34 ]. However, to our knowledge, few studies have investigated and compared the overall efficacy of DPP-4is and SGLT2is.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that both DPP-4is and SGLT2is exhibit a renal protective effect to reduce renal albumin and either improve or ameliorate the decrease in eGFR [ 30 32 ]. Administration of luseogliflozin decreased heart rate in Japanese patients with T2DM with higher heart rate [ 33 ], and switching from DPP-4is to luseogliflozin has been shown to decrease nighttime pulse rate [ 34 ]. However, to our knowledge, few studies have investigated and compared the overall efficacy of DPP-4is and SGLT2is.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested that the timing of medication-taking makes sense [14], while most Chinese patients take antihypertensive drugs in the morning. For antidiabetic agents, a meta-analysis showed that sodium-dependent glucose transporters 2 inhibitors (SGLT2i) reduced 24-hour BP in patients with diabetes and hypertension [29], and when changed from dipeptidyl peptidase-4 inhibitor to SGLT2i, the AR-BP signi cantly reduced [30]. Whether SGLT2i can reduce AR-BP and thus reduce the incidence of CAD in diabetic patients is the task we will undergo in the future.…”
Section: Discussionmentioning
confidence: 99%